Savings on the Cost of Production of Phinisi Ships in After-Sales Condition Through Quality Cost Budgeting - Muh Rum; Andi Muh. Nurjalal (www.amertainstitute.com, 2024)
This study aims to reduce the cost of production of phinisi ships by reducing after-sales claims through quality cost budgeting planning. Phinisi ships are products that have high cultural and economic value. However, in the production process, various risks can affect the quality and completion time. The research method used is quantitative descriptive using management accounting methods, and case studies of phinisi ship manufacturing in Bulukumba Regency, South Sulawesi. Data were collected through observation, interviews, and documentation studies. Data analysis includes identifying components of production costs, and quality costs, then calculating the present value per unit of ship time with quality costs and the present value per unit of ship time without quality costs. The results of the study indicate that quality costs in the production of phinisi ships can reduce the value of the cost of production. Can increase production efficiency in the long term. The present value of the ship with docking costs assuming an effective interest rate of 10% per year is obtained at Rp 2,332,815, while the ship produced without quality cost budgeting is obtained at a present value of Rp 53,494,941. So production costs can be saved by Rp. 51,162,125,-